Digesting the League of Nations: planning the international secretariat of the future, 1941-1944 - Auberer, Benjamin (New global studies, 2017)
This article examines the administrative debates on the structure of the post-war international order that took place during the Second World War. By focusing on a multinational study group composed of former high ranking League of Nations civil servants affiliated with the Royal Institute of International Affairs at Chatham House, it elucidates the activities of international civil servants after they left the League. It is shown how the group claimed to represent the experiences of the international secretariat of the League of Nations on a comprehensive scale by publishing a report on the evaluation of the League’s secretariat. An examination of the report investigates how the group defended the League of Nations and their own participation in the League.